Stabilitas Serum Kontrol Liofilisat Buatan Sendiri Setelah Rekonstitusi Terhadap Kadar Kolesterol dan Trigliserida yang Disimpan dalam Freezer Suhu (-2°C) sampai (-4°C) dan (-20°C) - Nada Nabilah Wulandari; Anik Handayati; Lully Hanni Endarini (Jurnal Penelitian Kesehatan SUARA FORIKES, 2023)
Lyophilisate control serum is a freeze-dried control serum. Control serum must be stable and can be examined for a long time in order to assess the performance of a laboratory, including the quality of tools and reagents. Cholesterol is a fat produced by the liver that causes heart disease in excess levels. Triglycerides are a form of fat storage in the body which functions as a source of energy. This study aimed to determine the stability of homemade lyophilisate control serum after reconstitution on cholesterol and triglyceride levels stored in the freezer at (-2°C) to (-4°C) and (-20°C). This study applied a one group post-test design. Samples were examined for 8 weeks with venous blood test material for lyophilisate control serum. The results of the analysis showed that cholesterol levels with storage for 8 weeks at temperatures (-2°C) to (-4°C) and (-20°C) were stable with an average within the range of ±2SD and CV between 1-6 %. Triglyceride levels with storage for 8 weeks at (-2°C) to (-4°C) were stable with an average within the range of ±2SD and a CV between 2-7%. R-square on the storage time of 8 weeks of lyophilisate control sera after reconstitution showed that storage time had a 16.35% effect on cholesterol stability at temperature (-2°C) to (-4°C), 0% on cholesterol stability at temperature (-20°C) ), 41.7% on triglyceride stability at temperature (-2°C) to (-4°C), and 32.52% on triglyceride stability at temperature (-20°C). The conclusion of this study is that the control sera of homemade lyophilisate after reconstitution with cholesterol and triglyceride parameters stored for 8 weeks is still stable and has a standard deviation within limits.Keywords: lyophilisate serum; reconstitution; cholesterol; triglycerides ABSTRAK Serum kontrol liofilisat merupakan serum kontrol bentuk beku kering. Serum kontrol harus stabil dan dapat diperiksa dalam jangka waktu yang lama agar dapat menilai kinerja suatu laboratorium, termasuk kualitas alat dan reagensia. Kolesterol merupakan lemak yang diproduksi oleh hati yang menyebabkan penyakit jantung dalam kadar berlebih. Trigliserida merupakan bentuk simpanan lemak dalam tubuh yang berfungsi sebagai sumber energi. Penelitian ini bertujuan untuk mengetahui stabilitas serum kontrol liofilisat buatan sendiri setelah rekonstitusi terhadap kadar kolesterol dan trigliserida yang disimpan dalam freezer suhu (-2°C) sampai (-4°C) dan (-20°C). Penelitian ini menerapkan one group post-test design. Sampel diperiksa selama 8 minggu dengan bahan uji darah vena untuk serum kontrol liofilisat. Hasil analisis menunjukkan bahwa kadar kolesterol dengan penyimpanan selama 8 minggu pada suhu (-2°C) sampai (-4°C) dan (-20°C) adalah stabil dengan rata-rata dalam batas rentang ±2SD dan CV antara 1-6%. Kadar trigliserida dengan penyimpanan selama 8 minggu pada suhu (-2°C) sampai (-4°C) adalah stabil dengan rata-rata dalam batas rentang ±2SD dan CV antara 2-7%. R-square pada lama penyimpanan 8 minggu serum kontrol liofilisat setelah rekonstitusi menunjukkan lama penyimpanan berpengaruh 16,35% terhadap stabilitas kolesterol suhu (-2°C) sampai (-4°C), 0% terhadap stabilitas kolesterol suhu (-20°C), 41,7% terhadap stabilitas trigliserida suhu (-2°C) sampai (-4°C), dan 32,52% terhadap stabilitas trigliserida suhu (-20°C). Kesimpulan dari penelitian ini adalah bahwa serum kontrol liofilisat buatan sendiri setelah rekonstitusi dengan parameter kolesterol dan trigliserida yang disimpan selama 8 minggu masih stabil dan mempunyai standar deviasi dalam batas.Kata kunci: serum liofilisat; rekontitusi; kolesterol; trigliserida